Hubungan Pengetahuan dan Sikap Terhadap Perilaku Masyarakat Dalam Upaya Pencegahan COVID-19 Di Kelurahan Bangkala Kecamatan Manggala Kota Makassar Tahun 2021 - harnilawati, harnilawati (Faculty of Medicine, Universitas Andalas, 2024)
Objective: to determine the relationship between knowledge and attitudes towards community behavior in efforts to prevent COVID-19 in Bangkala Village, Manggala District, Makassar City in 2021.Methods: The type of research used is an observational quantitative analytic study with a cross-sectional approach. The sampling technique used was accidental sampling. The sample was obtained by distributing online questionnaires in the form of a google form link that was distributed through social media, namely via whatsapp to the entire community of Bangkala Village, Manggala District, Makassar City, amounting to 376 people. Data analysis used Chi-square statistical test.Results: Based on the results of the chi-square test analysis, the p value on knowledge = 0.000 (<0.05) and the p-value on attitude = 0.000 (<0.05). This shows that there is a relationship between the level of knowledge and attitudes towards community behavior in efforts to prevent COVID-19.Conclusion: There is a relationship between knowledge and behavior of people in Bangkala Village, Manggala District, Makassar City towards efforts to prevent COVID-19. There is a relationship between attitudes towards community behavior in Bangkala Village, Manggala District, Makassar City towards efforts to prevent COVID-19.Â